Diabetes care : the status of diabetes care in Queensland residential aged facilities - DeBeyer, Carrie Jeanette (Curtin University, 2010)
Diabetes care of the elderly in residential aged care facilities has often been unstructured and non-standardised, with disparities in both the practice and knowledge of health care workers caring for this vulnerable group. Poorly controlled diabetes can contribute to a range of adverse events, including impaired wound health and cardiovascular events. The purpose of this study was to establish if current Australian diabetes management guidelines for the elderly are being met in residential aged care facilities in Queensland and identify areas for clinical practice improvement.A cross-sectional, descriptive design was employed to measure demographic data, perceived and actual diabetes-related knowledge, availability of diabetes management and care guidelines, and facilitators and barriers to meeting diabetes related care. A sample of 109 health care workers from residential aged care facilities completed a postal survey.Diabetes guidelines shown to be available in residential aged care facilities were aimed at care planning, with guidelines for both screening and monitoring of diabetes and diabetes care specific skills more available in private aged care and high care classified facilities. Limited monitoring of outcomes of diabetes care were evident. Overall, participants perceived their diabetes knowledge as “good”, however deficits were found in the level of actual knowledge on diabetes complications and medication management. Ratings for perceived and actual diabetes knowledge was higher with older aged health care workers by those employed in their current position the longest.Furthermore, a positive relationship was shown between perceived and actual diabetes knowledge with years of experience in aged care, employment status (RNs/ENs, AINs and other health care workers) and education status (grade 12 schooling, Technology and Further Education and university award). Diabetes – related knowledge was shown to be the most significant facilitator as well as barrier to diabetes care provision. Factors affecting perceived level of confidence in providing diabetes self-management education included experience in aged care, employment position and level of education.The contribution of this research to the area of study was to provide important data on the availability of diabetes guidelines and protocols and diabetes knowledge base. Data has also been provided for the availability of diabetes guidelines and protocols in different facility types and with different classifications of care as well as data for the perceived level of confidence in providing diabetes care in residential aged care facilities. Study findings indicate a need for an increased focus on diabetes care in residential aged care to improve health outcomes.